(untitled) (Journal of the College of Basic Education, 2025)
The meaning of life is the cognitive system that the individual forms about the personal experiences that have passed through his life and that the meaning system includes three components (cognitive, motivated, and emotional). the meaning of life humanitarian experience that a person seeks to reach, to give his life a value and meaning worth living for and occur as a result of satisfying his motive based on the will of meaning. A lot of people live in life without meaning . . The research aims to identify the level of meaning of life among students of special education, and the significance of differences in the meaning of life according to the gender variable. The researcher adopted the scale of the meaning of life designed by (Crumbo and Mahulk, 1964), relying on the concepts of theory (Frankl), consists of (20) incomplete paragraph prepared in the style of verbal report completed through alternatives answer seven according to the method of Likert, two phrases complement the paragraph and in the middle point of neutrality. The research sample of( 100) male and female students was selected using a simple random method from the Special Education at all levels equally .There validity and reliability of the scale were extracted , The results showed and that the students suffer from existential emptiness or moral void, and there were also significant differences in favor of the doctor in the meaning of life. The most important recommendations: to conduct training courses and guidance programs that enhance the meaning of life for students